Value co-creation in maintenance services: case study in the mechanical industry. Issue 5 (4th September 2017) - Braun, Eduardo Luiz; Pereira, Giancarlo Medeiros; Sellitto, Miguel Afonso; Borchardt, Miriam
Abstract : Purpose: The purpose of this paper is to analyze a contract-based relationship for value co-creation and gain-sharing between two companies for the purpose of industrial maintenance services. After five years of good results for both parties, the relationship was terminated, thus raising questions regarding on the actual gains shared by both partners from joint actions. Design/methodology/approach: The research method is the longitudinal case study. The research question is: why would a contractual relationship of co-creation of value be terminated given the fact that it yielded good financial results for both parts over the course of five years? The main research techniques were structured interviews with relevant actors and documental analysis from both parts involved in the contract. Findings: Even valuable contracts can be terminated if the external scenario changes significantly: it matters very little the good job done together if the result became poor due to external reasons, as buyer's sales drop in the period. In the inner scenario, mistruth can arise if the buyer maintains parallel structures for performing similar tasks to those of the service provider, showing some kind of independence from the supplier. Research limitations/implications: The main limitation is that inherent to case studies: the lack of generalization. Practical implications: When companies decide to contract regular long-term maintenance services, preventions to revenue reductions of the main activity the must be present, for the continuity of the contract. Originality/value: To the date of this research, no similar study was found, regarding the influence of the external results in the internal relationships in co-creation value contracts.